Quantum Dots Synthesis Through Direct Laser Patterning: A Review - Antolini, Francesco; Orazi, Leonardo (Frontiers in Chemistry, 2019)
In this brief review the advances on Direct Laser Patterning (DLP) for the synthesis of photo-luminescent semiconductor quantum dots (QDs) belonging to II-VI groups, especially in solid state using laser-assisted conversion are reported and commented. The chemistry of the precursor synthesis is illustrated because it is a crucial step for the development of the direct laser patterning of QDs. In particular, the analysis of cadmium (bis)thiolate and cadmium xanthates precursors after thermal and laser treatment is examined, with a special focus on the optical properties of the formed QDs. The second part of the review examines how the laser parameters such as the wavelength and pulse duration may regulate the properties of the patterned QDs. The DLP technique does not require complex laser systems or the use of dangerous chemical post treatments, so it can be introduced as a potential method for the patterning of pixels in quantum dot light emitting diodes (QD-LEDs) for display manufacturing.